SOME REMARKS REGARDING PHOTOELECTRIC PHOTOMETRY - MENDOZA, EUGENIO (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1970)
Photoelectric photometry of faint stars in the Orion Nebula present serious difficulties due to the brightness of the nebula and its surface variation. In the present work we describe in detail the techniques followed during flare star observations. The m
BOL OBS TONAN TACUB
Keywords: REMARKS, REGARDING, PHOTOELECTRIC, PHOTOMETRY; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS